2013
DOI: 10.1080/00380768.2013.806205
|View full text |Cite
|
Sign up to set email alerts
|

Biochar derived from dairy cattle carcasses as an alternative source of phosphorus and amendment for soil acidity

Abstract: Two pot experiments were conducted to evaluate biochar derived from dead dairy cattle as a mineral fertilizer, especially phosphorus (P) fertilizer, and to clarify the effect of particle size of biochar on plant growth (Zea mays L.) and P uptake. To produce the biochar, body parts of dead cattle were placed in a charring chamber and allowed to char at 450°C for 4 h. The biochar was of high pH and rich in major plant nutrients, especially P. Application of fine biochar (< 1 mm) increased P uptake by the corn pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 15 publications
6
13
0
2
Order By: Relevance
“…However, nano‐ or micro‐sized P‐fertilizers provide large specific surface areas that promote their possible attachment to solid soil surfaces . The results of the present incubation‐leaching study are also consistent with those from Ma and Matsunaka who examined three size fractions (<1, 1–2, and 2–4 mm) of biochar (pyrolyzed meat and bone meal from dairy cattle) in a pot experiment. The <1 mm size‐fraction of biochars was most effective to increase P‐dissolution and subsequently promote plant growth.…”
Section: Resultssupporting
confidence: 89%
“…However, nano‐ or micro‐sized P‐fertilizers provide large specific surface areas that promote their possible attachment to solid soil surfaces . The results of the present incubation‐leaching study are also consistent with those from Ma and Matsunaka who examined three size fractions (<1, 1–2, and 2–4 mm) of biochar (pyrolyzed meat and bone meal from dairy cattle) in a pot experiment. The <1 mm size‐fraction of biochars was most effective to increase P‐dissolution and subsequently promote plant growth.…”
Section: Resultssupporting
confidence: 89%
“…This is consistent with the study of according to which the BC application (< 90 µm BC thoroughly mixed in soil) significantly increased the insoluble P proportion (H 2 SO 4 -P). Additionally, our study confirmed previous findings concerning the effect of particle sizes on the P release from BCs (Morshedizad and Leinweber, 2017) and consequently the P status of treated soils (Ma and Matsunaka, 2013). Sequentially extracted P contents increased with the decreasing size of BC particles whereby BC plus treatments appeared more dependent on particle size than BC treatments.…”
Section: P Availability As Revealed By Sequential Fractionationsupporting
confidence: 81%
“…This is consistent with the study of according to which the BC application (<90 µm BC thoroughly mixed to soil) significantly increased the insoluble P proportion (H2SO4-P). Additionally, our study confirmed previous findings concerning the effect of particle sizes on the P release from BCs (Morshedizad and Leinweber, 2017) and consequently the P status of treated soils (Ma and Matsunaka, 2013). Sequentially extracted P contents increased with decreasing size of BC particles whereby BC plus treatments appeared more dependent on particle size than BC treatments.…”
Section: P Availability As Revealed By Sequential Fractionationsupporting
confidence: 91%